Is There a Relation Between Triglyceride Concentrations in Very Low Density Lipoprotein and the Index of Insulin Resistance in Nondiabetic Subjects? - Kurosaki, Yoshifumi (J Clin Lab Anal, 2014)
BACKGROUND: Serum very low density lipoprotein (VLDL) levels increase during the early stages of insulin resistance; therefore, determination of VLDL levels would be useful for evaluating the progression of metabolic syndrome and diabetes mellitus. The aim of this study was to clarify the clinical utility of triglyceride in VLDL (VLDL‐TG) level, determined using a homogeneous assay kit (Shino‐test Corporation, Tokyo, Japan), as an index of insulin resistance. METHODS: We enrolled 74 subjects in this study (diabetic subjects, n = 42; nondiabetic subjects, n = 32). The levels of VLDL‐TG, remnant‐like lipoprotein particle cholesterol, preheparin lipoprotein lipase mass, and other biochemical markers were determined. RESULTS: VLDL‐TG levels were significantly higher in the diabetic group (1.04 ± 0.84 mmol/l vs. 0.64 ± 0.42 mmol/l, P < 0.01) than in the nondiabetic group. In the nondiabetic group, VLDL‐TG was significantly correlated with the homeostasis model assessment of insulin resistance (HOMA‐IR), the index for insulin resistance (r = 0.513, P = 0.003). VLDL‐TG levels, but not TG levels, were higher in the highest quartile (HOMA‐IR) of the nondiabetic group. CONCLUSION: VLDL‐TG level was a useful early marker for insulin resistance, especially in nondiabetic subjects. The homogeneous VLDL‐TG assay is a simple, low‐cost method for determining insulin resistance.